Motivational Factors of Parents in Choosing Islamic-Based Kindergarten and Its Relationship with Strengthening Religious Moral Values in Early Childhood - Zakiyyah, Nurul (Aulad: Journal on Early Childhood, 2024)
This study was motivated by the emergence of a decline in moral attitudes and lack of religious awareness, especially Islamic religion in children and adolescents in Indonesia. The purpose of this study was to determine the motivational factors and strengthening of moral and religious values provided by Islamic-based Kindergarten. The research approach used was qualitative with descriptive method. This research was conducted in one of the Islamic-based Kindergarten in Cimahi City with eight research participants of parents of students. Data collection techniques were conducted through interviews, observation and documentation. The results show that the intrinsic factors motivating parents to choose Islamic-based Kindergarten are the desire for children to understand religion, close to the Qur'an, pious, have good manners and be able to take care of themselves. The extrinsic factors are strategic school location, alumni achievement, good environment, alternative activities for student guardians and quality of religious learning programms. The implication of this research is expected to provide recommendations to the school to optimise the factors that are proven to influence the motivation of parents in choosing Islamic-based schools for their children.